KEPEMIMPINAN DALAM PENDIDIKAN : ANALISIS FUNGSI, GAYA DAN PRINSIP – PRINSIP DALAM PERSPEKTIF ISLAM - Halimah, Dewi Nur; Ubaidillah, Fasichah; Izzati, Erica Wahyu; Aprilia, Fira Wulandari; Mardhiyah, Mardhiyah (at-Tahsin, 2025)
Leadership is the ability to influence, guide, and direct others towards achieving specific goals. This concept is explored from two viewpoints: the general perspective and the islamic perspective. From a general standpoint, leadership is seen as a process of interaction between leaders and followers aimed at achieving shared objectives. In contrast, from an islamic perspective, leadership encompasses both moral and spiritual dimensions, grounded in the teachings of the Quran and Hadith. Leadership serves two key functions. Generally, it involves guiding, coordinating, and motivating individuals within an organization or society. In islam, however, leadership extends beyond worldly matters to include responbilities for the welfare and justice of the people, all in accordance with sharia principles. In addition, the leadership style applied by a leader can vary. In a general context, leadership styles consist of authoritarian, democratic, and laissez-faire, each of which has its advantages and disadvantages. In Islam, leadership style emphasizes more on traits such as justice, trustworthiness, deliberation, and exemplary behavior, as exemplified by the Prophet Muhammad SAW. Leadership principles are also an important aspect in this discussion.